2011
DOI: 10.4028/www.scientific.net/amr.341-342.26
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Wear Behavior of Brake Pads Produced from Palm Slag

Abstract: Brake pads are important safety devices in vehicles. An effort to avoid the use of asbestos in brake pads has led to the development of asbestos-free brake pads that incorporate various organic and inorganic fillers. Palm slag as a filler in brake pads was investigated in this paper. Different processing pressures were employed during production of samples through compression molding. The properties examined included hardness, compressive strength, and wear behavior. The results showed that brake pad samples p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Idris et al [ 44 ] determined the Brinell hardness value for banana peel waste/phenolic resin to replace asbestos. Ruzaidi et al [ 45 ] studied the hardness of a palm slag filler (asbestos-free) brake pad using the Rockwell hardness test. Rashid et al [ 46 ] investigate the Rockwell hardness characteristics of SPF/Phenolic composites and indicate that as the SPF loading in the composites increases, Rockwell hardness decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Idris et al [ 44 ] determined the Brinell hardness value for banana peel waste/phenolic resin to replace asbestos. Ruzaidi et al [ 45 ] studied the hardness of a palm slag filler (asbestos-free) brake pad using the Rockwell hardness test. Rashid et al [ 46 ] investigate the Rockwell hardness characteristics of SPF/Phenolic composites and indicate that as the SPF loading in the composites increases, Rockwell hardness decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 depicts an ABS motorcycle battery housing component that was used to compare the various characteristics of the current ABS motorcycle battery housing component with the proposed SPF/GF/PLA hybrid composites. Sherwani et al [ 45 ] showed that 70% PLA and 30% SPF exhibit good mechanical properties, primarily tensile and flexural characteristics; thus, a 70% PLA to 30% fiber ratio is considered in this research. Recently, Sherwani et al [ 50 ] investigated the effect of three alkaline solution concentrations of 4%, 5%, and 6% for alkaline treatment, and 50 mL benzoyl chloride-treated SPFs at three different soaking durations of 10, 15, and 20 min on SPF/PLA composites and found that the best percentage is 6% alkaline and the best soak time is 15 min for improving mechanical properties of SPF/PLA composites.…”
Section: Introductionmentioning
confidence: 99%
“…Along with additional friction additives, phenolic resins were employed as binders. Within the temperature range of 50 °C to 1000 °C, the thermal characteristics, compressive strength, and wear behavior demonstrated stability and excellent performance [19].…”
Section: Print Issn 2714-2469: E-issn 2782-8425 Uniosun Journal Of En...mentioning
confidence: 99%
“…Graphite (10), Steel Fiber (20), Alumina (10) Graphite (10), Steel Fiber (20), Alumina (10) Graphite (10) In a study conducted by (Ruzaidi-Gazali, et al, 2012) [15] palm slag was investigated as a filler for brake pads. Palm slag at 40 wt% was mixed with phenolic resin at wt%, and the remaining 40 wt% consisted of graphite, steel fiber, and alumina.…”
Section: Palm Slagmentioning
confidence: 99%